Analysis of the Financial Performance of the Regional Government of Pohuwato Regency - K. Usman, Mohammad Reiffly (Raudhah Publisher, 2025)
This study aims to analyze the financial performance of the Pohuwato Regency Regional Government during the 2018-2022 period, with a focus on the impact of the Covid-19 pandemic on regional financial management. The methods used include financial ratio analysis, which includes the ratio of independence, effectiveness, efficiency, and degree of fiscal decentralization. The results of the study show that during the pandemic, there was a significant shift in regional expenditure allocation, where operational expenditure increased while capital expenditure decreased. The regional financial independence ratio shows a high dependence on transfers from the central government, while Regional Original Revenue (PAD) has stagnated. This study also found that budget management through the Regional Revenue and Expenditure Budget (APBD) needs to be improved to ensure a more optimal allocation of funds in supporting development programs. This finding is expected to provide recommendations for local governments in formulating policies that are more effective and responsive to the needs of the community and increase regional competitiveness. Thus, this financial performance analysis is important in order to achieve sustainable development goals in Pohuwato Regency.